Cell-attached single-channel recordings in intact prefrontal cortex pyramidal neurons reveal compartmentalized D1/D5 receptor modulation of the persistent sodium current - Gorelova, Natalia; Seamans, Jeremy K. (Frontiers in Neural Circuits, 2015)
The persistent Na current (INap) is believed to be an important target of dopamine modulation in prefrontal cortex (PFC) neurons. While past studies have tested the effects of dopamine on INap, the results have been contradictory largely because of difficulties in measuring INap using somatic whole-cell recordings. To circumvent these confounds we used the cell-attached patch-clamp technique to record single Na channels from the soma, proximal dendrite or proximal axon of intact prefrontal layer V pyramidal neurons. Under baseline conditions, numerous well resolved Na channel openings were recorded that exhibited an extrapolated reversal potential of 73 mV, a slope conductance of 14-19pS and were blocked by TTX. While similar in most respects, the propensity to exhibit prolonged bursts lasting >40ms was many fold greater in the axon than the soma or dendrite. Bath application of the D1 agonist SKF81297 shifted the ensemble current activation curve leftward and increased the number of late events recorded from the proximal dendrite but not the soma or axon. However, the greatest effect was on prolonged bursting where the D1 agonist increased their occurrence 3 fold in the proximal dendrite and nearly 7 fold in the soma, but not at all in the axon. As a result, D1 activation equalized the probability of prolonged burst occurrence across the proximal axosomatodendritic region. Therefore, D1 modulation appears to be targeted mainly to Na channels in the proximal dendrite/soma and not the proximal axon. By circumventing the pitfalls of previous attempts to study the D1R modulation of INap, we demonstrate conclusively that D1R can increase the INap generated proximally, however questions still remain as to how D1R modulates Na currents in the more distal initial segment where most of the INap is normally generated.